The readiness of public libraries in South Africa for information literacy education: the case of Mpumalanga Province - Hart, Genevieve Claire (Department of Knowledge and Information Stewardship, 2023)
The purpose of the study is to investigate the readiness of public libraries in South Africa for an enhanced educational role in developing the information literacy of school learners. The public libraries in Mpumalanga Province provide the case site for the study. Across the world, information literacy education has been identified as the raison d'etre of school libraries. There are two arguments for public libraries in South Africa to take on this mission: • the demands of the global economy for information literate school leavers - reflected in South Africa's new school curriculum, which is widely described as "resource-based" and which lists infonnation skills as a critical cross-curricular outcome • the shortage of school libraries in South Africa. It has been estimated that eight million out of 12 million learners do not have access to libraries in their schools. In recent years there have been suggestions that South African public libraries take on a more direct educational and developmental role - which might be more appropriate than the inherited Western model of service. Information literacy education might well be their unique contribution to social inclusion in a country where, on average, less that 10 percent of the population belong to public libraries. The introduction in the late 1990s of the new curriculum has brought a huge increase in the use of public libraries by school learners - most of whom are not signed-up members but who need access to public library resources as they grapple with the information seeking demands of their school projects and assignments. The increase in use has led to much comment in public library circles on the iJJ-preparedness of school learners for project work in the library. The theoretical underpinning of the study comes from the research and theory building of Carole Kuhlthau and Christine Bruce - both of whom have enriched information literacy theory with their "borrowing" from constructivist and relational learning theory. To Kuhhhau, information literacy is a constructive process of building meaning and knowledge. The task of information literacy education in schools and libraries - is to teach people how to learn - not how to find discrete bits of information. Christine Bruce's research highlights the significance of people's conceptions of information and information literacy. She identifies categories of conceptions ranging from those which see information literacy as knowing about resources to those who describe it as creating new knowledge and building wisdom. Effective information literacy education has to take into account the existence of these different conceptions. The PhD study sets out to examine if indeed public libraries in South Africa might assume an enhanced responsibility for information literacy education and, if so, what inhibiting and 111 facilitating factors might exist. The word "readiness" in its title has two layers of meaning: at one level it refers to physical capacity and on a second level to more intangible and subjective attributes such as staff attitudes and beliefs. The research questions examined in the study relate to these two layers of meaning. They are informed also by a wide-ranging survey of the literature of educational change in South Africa and of the role of public libraries, internationally, in information literacy education. The questions can be grouped into three categories: • What is happening at present in terms of information literacy education for school learners? • Do public libraries have the physical capacity for information literacy education? • What are the attributes of public library staff in terms of their experience of and attitudes towards information literacy, information literacy education, and, indeed, towards a stronger educational role for public libraries? Any discussion on the capacity of Mpumalanga's public libraries for information literacy education has immediately to acknowledge the uneven distribution of libraries - common to all South African provinces. The Director of Mpumalanga Provincial Library Service estimates that his province requires 98 new libraries. The Province of Mpumalanga lends itself to the research problem for a number of reasons. Its social and economic characteristics throw into relief the critical issues highlighted in the literature review. It is one of South Africa's five "new'' provinces, having amalgamated two apartheid era "homelands". It is regarded as a "rural" province" with sprawling densely populated but underdeveloped areas. Only 18 percent of its schools have libraries. The study took place in a time of upheaval and restructuring of local government - the tier of government responsible for the day to day management of public libraries. The climate of uncertainty is found to play a significant part in the prevailing low morale of public library staff. The research project has a design structure of two interdependent phases. The overarching theoretical framework is interpretivist constructivism. The realities and meanings constructed by public library staff are central to the problem. However, it employs both qualitative and quantitative methodologies as each contributes to the understanding of the problem. The first phase is a broad survey of 46 public libraries in Mpumalanga, undertaken in March/April 2004, which gathers both qualitative and quantitative data by means of interviews with 57 staff members - based on a semi-structured questionnaire. The aim was to gather quantitative data on the resources and facilities within the libraries and their services to schools - and, by means of several open-ended questions, qualitative data on library staff views on the impact JV of the new curriculum and possible changes in their social role. The first phase leads into the next phase - a more focused participant observation case study of the information literacy programmes in two public libraries in one small town throughout October 2004. Three vignettes scaffold the case study, which serve both to give a sense of context and to highlight the theoretical issues. In this phase, an added perspective is school educators' use of the library - and their beliefs about learning and libraries. Twenty-seven interviews with Grade 7 and 8 educators and principals in the seven schools served by the public libraries were conducted. The analysis of the first phase data led to tentative findings. The second phase case study started afresh - open to alternative or contradictory interpretations. However, its findings are surprisingly convergent with those of the first phase. It seems that Mpumalanga public libraries are heavily engaged in serving school learners. The study indeed concludes that public libraries need school learners - given their low use by adults. Shortcomings in certain physical facilities, such as the lack of space and absence of retrieval tools, are inhibiting factors with the heritage of apartheid still impacting on the availability of and quality of service. The low level of professional education of public library staff is found to impede innovation in library and information service programming. The prevailing information literacy education largely comprises, at present, one-to-one support, although there is a fair amount of source-based group library orientation. Moving from library orientation towards information literacy education will depend on a shift in conceptions of the educational role of public libraries. In the absence of recognition of their curricular role by public library authorities and educationists, many public librarians are not sure that their services to school learners are legitimate. There is, at the same time, dawning recognition that present approaches are not meeting the needs of school learners and that more effective communication with educators is required. This recognition comes from public librarians' frustrating encounters with learners rather than from insight into information literacy education theory and experience. And educators' simplistic conceptions of project work and lack of cognizance of the demands of information seeking in the library do not allow for a more dynamic role for public libraries. The study makes recommendations for various role-players - the library profession, the governance structures of public libraries, public library staff, educators and educationists, and information literacy researchers. The fundamental conclusion is that sustainable information literacy education in public libraries will depend on more dynamic leadership and on a vision of a new model of public library.